Lowering B-type natriuretic peptide levels and increasing cardiac function: the role of levosimendan in the treatment of heart failure - Jianfeng Meng; Ye Zuo (Journal of International Medical Research)
Objective In this study, we examined whether levosimendan could lower B-type natriuretic peptide (BNP) and improve cardiac function in patients with heart failure who have diuretic resistance and low ejection fraction. Methods We conducted a cohort study among 120 participants from September 2022 to August 2023. We investigated the efficacy of treatment with levosimendan in patients with HF who exhibited diuretic resistance and had a low ejection fraction. All patients received recombinant human neuronal natriuretic peptide (rhBNP) and the treatment group additionally received levosimendan. In addition to the primary endpoints, safety measures were assessed, encompassing the monitoring of blood pressure, heart rate, and serum creatinine levels. Results Patients in the treatment and control groups were similar in age, sickness duration, weight, and sex ratio. Medication use, New York Heart Association classification, ejection fraction percentage, and other factors were evenly distributed. The treatment group showed increased urine volume and weight loss. Both groups had similar post-treatment systolic blood pressure, heart rate, and serum creatinine levels, indicating good safety. Conclusion Levosimendan in combination with rhBNP may improve diuretic resistance in patients with HF and low ejection fraction. Further multicenter trials are needed to confirm our findings.